Exceptionally preserved lacustrine ostracods from the Middle Miocene of Antarctica: implications for high-latitude palaeoenvironment at 77° south - Williams, Mark (The Royal Society, 2008)
A newly discovered Konservat-Lagerstätte from the Middle Miocene of the western Olympus Range, Dry Valleys, Antarctica, yields cypridoidean ostracods complete with preserved body and appendages. This is the first record of three-dimensionally fossilized animal soft tissues from the continent. The ostracods are preserved in goethite, secondary after pyrite, representing a novel mode of exceptional preservation. They signal a high-latitude (greater than 77° south) lake setting (Palaeolake Boreas) viable for benthic animal colonization prior to 14 Myr ago. Their presence supports the notion of warmer, tundra-like environmental conditions persisting in the Dry Valleys until the Middle Miocene.